Peningkatan Motivasi Belajar dan Prestasi Belajar Pendidikan Karakter Nilai Kedisiplinan Melalui Pembelajaran Tematik Pada Peserta Didik Kelas III Sekolah Dasar - Agung Apriliarso Pujiwibawa; Samsi Haryanto; Sri Yamtinah (Universitas Sebelas Maret, 2017)
The purpose of this research is to enhance learning motivation and learning achievement of character education in disciplinary values in grade III students of SDN 2 Japan, Dawe, Kudus 2014/2015 Academic Year. This research is a classroom action research consisting of two cycles including planning, implementation, observation, and reflection. The subjects of the study are 25 of Students. Data are obtained using interviews, documentation and questionnaire. Data analysis techniques used are qualitative descriptive. The results of the classroom actionresearch show that; 1) Application of thematic learning with the Contextual Teaching and Learning approach can appropriately increase motivation and learning achievement of character education in the discipline value of students in Elementary School 2 Jepang, Dawe sub-district, Kudus 2014/2015 Academic Year. Based on the results of the distribution of questionnaires on students' learning motivation, it was found that the success target of cycle I (76%) increased in cycle II to (96). 2) The advantage of thematic learning with the Contextual Teaching and Learning approach is that learning becomes more meaningful because students are shown the material concepts with the real world experienced in everyday life. The weaknesses students are hesitant in expressing their opinions.